The Washback of Formative Assessment on Summative Assessment: Students’ Perception - Kanar Zirak Haseeb Chicho; Mowafaq Muhammed Al-kassab; Soma Hassan Hussein (International Journal of Social Sciences & Educational Studies)
Exams are a crucial component of the educational system. The significance of exams must be considered by stakeholders. As exams are a part of assessment and evaluation, and they impact the study program, students, and teachers. Testing and evaluation’s impact on students and teachers is known as washback. In many regions Exams are tools for deciding on students passing from one grade to another. Therefore, students study to pass examinations rather than learn the course goals because of the negative washback from exams. Positive washback, on the other hand, encourages pupils to study harder and learn more. This study explores students’ perceptions regarding the washback of the midterm exam (formative) on final exams (summative). A quantitative methodology was chosen to fulfil the aims of this study by distributing an online survey. With the responses from 108 participants the impact of these variables gender, age, and department were the focus of this paper. The findings showed that there are no significant differences between these variables gender, age, department. In brief, students will always have the same washback positive or negative no matter no matter their ages, gender and department. Thus, this study suggests that the student’s perception on exam washback should be considered rather their age, gender or department.